Estimating Loyalty and Switching with an Application to the Automobile Market - McCarthy, Patrick S.; Kannan, P. K.; Chandrasekharan, Radha; Wright, Gordon P. (Management Science, 1992)
A brand switching model that considers the choices: previous choice, current choice, and substitute choice, if the current choice were not available, is developed and estimated. An important assumption of the model is that the market consists of two types of consumers: “Loyals” and “Shoppers.” The model provides estimates for: (1) the proportion of Loyals in a submarket, and (2) the success of each submarket in capturing Shoppers. We illustrate how the model can be used to characterize the competitive structure of a market. We also show how the estimated parameters of the model can be validated using simulation and a theoretically derived covariance matrix. Our empirical application to automobile data from J. D. Power and Associates provides insights into several interesting marketing phenomena including: (1) the competitiveness of domestic versus foreign makes of automobiles, (2) competition between submarkets defined by form, and (3) the effect of previous dealer experience on loyalty and shopping.